Knee overuse injuries in cyclists - Pimentel, Sabrina; Interna de Formação Específica em Medicina Física e de Reabilitação; Hospital de São João E.P.E., Porto, Portugal. (2013)
In cyclists, overuse injuries are quite common; the knee is one of the most frequently affected anatomical sites. Knee overuse injuries can be caused by several factors and are sometimes associated with changes in mode, intensity or duration of training. Knee pain is the main clinical manifestation. In decreasing order of frequency and according to its location, knee pain can be classified as anterior, lateral, medial and posterior knee pain. An adequate approach to these injuries includes the establishment of a correct anatomical and pathological diagnosis as well as the identification and correction of intrinsic or extrinsic predisposing factors. As these injuries have a significant functional impact, their prevention seems more relevant than their treatment. Keywords: Bicycling, Cumulative trauma; Athletic Injuries; Knee injuries.